2020
DOI: 10.1016/j.metabol.2020.154324
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin promotes beta cell regeneration by inducing pancreatic endocrine cell phenotype conversion in type 2 diabetic mice

Abstract: Background: Clinical trials and animal studies have shown that sodium-glucose co-transporter type 2 (SGLT2) inhibitors improve pancreatic beta cell function. Our study aimed to investigate the effect of dapagliflozin on islet morphology and cell phenotype, and explore the origin and possible reason of the regenerated beta cells. Methods: Two diabetic mouse models, db/db mice and pancreatic alpha cell lineage-tracing (glucagon-β-gal) mice whose diabetes was induced by high fat diet combined with streptozotocin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 53 publications
3
49
1
Order By: Relevance
“…6 e,h). However, we still cannot deny the involvement of re-differentiation of β-cells, α- to β-cell conversion and the influence of humoral factors as previously reported 42 , 43 . It still needs further investigation to clarify this point.…”
Section: Discussioncontrasting
confidence: 63%
“…6 e,h). However, we still cannot deny the involvement of re-differentiation of β-cells, α- to β-cell conversion and the influence of humoral factors as previously reported 42 , 43 . It still needs further investigation to clarify this point.…”
Section: Discussioncontrasting
confidence: 63%
“…Alloxan and caerulein treatment induced trans-differentiation of α-cells into β-cells, and further induction into δ cells in murine and human T1DM [ 31 ]. In particular, treatment with dapagliflozin, the sodium-glucose co-transporter type 2 (SGLT2) inhibitor, induced α-to-β-cell trans-differentiation and promoted duct-derived β-cell neogenesis partially mediated via glucagon-like peptide-1 (GLP-1) in mice [ 32 ]. Therefore, regeneration of β-cells by inducing trans-differentiation from other cell types is an attractive therapeutic option for both types of diabetes.…”
Section: Trans-differentiation Of Pancreatic β-Cellsmentioning
confidence: 99%
“…Robust clinical evidence [ 70 , 71 ] on the β-cell protection afforded by SGLT2 inhibitors has been documented, with several relevant mechanisms proposed, including deceleration of β cell death and regeneration of pancreatic islet cells via amelioration of glucotoxicity, lipotoxicity, inflammation, fibrosis, and oxidative damage [ 63 , 72 ]. Furthermore, Wei et al reported that SGLT2 inhibitors induced β-cell self-replication, α-to-β cell conversion, and duct-derived β cell neogenesis in an animal model, partially mediated by the additional promotion of glucagon-like peptide-1 (GLP-1) secretion [ 73 ]. Finally, the attenuative effects of SGLT2 inhibitors on oxidative stress and inflammatory responses are also crucial for restoring insulin sensitivity, as discussed above.…”
Section: Sglt2 Inhibitors As Antioxidants In Diabetesmentioning
confidence: 99%